Characteristics and Relationship Between Eco-Literacy Competencies and Independent Curriculum Indonesian Language Learning Objectives Middle School Level in Indonesia - Farahiba, Ayyu Subhi; Puspitasari, Mega; Khotimah, Khusnul; Pramithasari, Febi Ayu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
The research aims to examine the characteristics of eco-literacy-based Indonesian language learning and to design a link between eco-literacy competencies and the objectives of Indonesian language learning in the Merdeka curriculum at the junior high school level as a curative solution to overcome environmental problems in Indonesia. This study uses a qualitative approach with design as a content analysis of the latest curriculum documents in Indonesia. The data collection technique is the documentation technique, using data sources from independent curriculum documents at the junior high school level. To obtain valid and reliable data, reading, listening, and analyzing basic competencies that intersect with environmental education are done. The data analysis technique is organization, synthesis, and identification. The research results show that ecoliteracy-based Indonesian language learning strategies include problem-solving, simulations, demonstrations, environmental-themed projects, discovery-based learning, and experiments. All Indonesian language learning texts in classes VII and VIII include head, hands, and heart aspects. The head aspect is related to learning objectives in the cognitive domain, which requires students to master the ability to identify, interpret, compare, and analyze environmentally friendly texts. The hand aspect is related to learning objectives in the psychomotor domain which requires students to be able to practice, write, and speak in accordance with environmentally friendly texts. The heart aspect is related to learning objectives in the affective domain, namely, requiring students to empathize with environmental issues.